Design and Analysis of I-Slotted Rectangular Microstrip Patch Antenna for Wireless Application - Kuldeep Kumar Parashar (Institute of Advanced Engineering and Science, 2014)
This paper presents a novel design of a I- slotted patch antenna with compact nature and the study of various antenna parameters. The antenna is fed by inset feeding technique. The proposed patch antenna is designed and simulated on IE3D simulation software. The main aim of proposed work is to obtain a large bandwidth antenna with compact size. The proposed microstrip antenna has a wide bandwidth covering the range from 1.444-2.393 GHz. By using simple Inset feed technique & by introducing I-slotted wide bandwidth of 49.46%, High Gain 5dBi & good radiation efficiency of about 99% has been achieved.DOI:http://dx.doi.org/10.11591/ijece.v4i1.4594